Author Correction: Increasing extreme melt in northeast Greenland linked to foehn winds and atmospheric rivers (Nature Communications, (2023), 14, 1, (1743), 10.1038/s41467-023-37434-8) - Mattingly, Kyle S.; Turton, Jenny; Wille, Jonathan D.; Noël, Brice; Fettweis, Xavier; Rennermalm, Åsa K.; Mote, Thomas L. (Nature Communications, 2024)
Correction to: Nature Communications, published online 29 March 2023 The original version of this Article contained an error in the “Introduction”, which incorrectly read ‘The Greenland Ice Sheet (GrIS) has lost 3.9 billion tons of ice since 1992.’ The correct version states ‘ 3,900 billion tons’ in place of ‘ 3.9 billion tons’. This has been corrected in both the PDF and HTML versions of the Article.
CRIS-Team Scopus Importer:2024-01-12